Magika hiera : ancient Greek magic and religion - Faraone, Christopher A.; Obbink, Dirk (Oxford University Press, 1997)
This is a collection of essays by leading American and European scholars. Its purpose is to remedy the tendency among scholars working in Greek religion to ignore the evidence for what have traditionally been called "magical" practices in ancient Greece. Because this neglect seems to arrive from adherence to a preconceived notion about a clear dichotomy between magical and religious ritual, the editors focus on the relationship between these two areas.